THE EFFECT OF ADDING MAGGOT BSF (Black Soldier Fly) FLOUR WITH DIFFERENT LEVELS ON PERFORMANCE STARTER PHASE BROILER CHICKEN - Triandoyo, Andre; Wulandari, Eudia Christina; Sunu, Prayogi (Universitas Boyolali, 2022)
Broiler chickens are the result of a livestock breeding process that aims to obtain poultry commodities with good growth performance. Broiler chicken productivity is influenced by rations, seeds and maintenance management. The efficiency of the use of feed ingredients in the ration is a major factor in broiler farming business. BSF (black soldier fly) maggot flour has good potential and is supportive in this regard. The material used is 60 broilers aged 1 day using DOC Superchick. Completely randomized method with unidirectional pattern with 4 treatments, 5 replications, each replication consisted of 3 tails. This study calculates the amount of Feed Conversion Ratio (FCR) using a manual system and using partner guidelines in determining the FCR number in calculating mortality is carried out every 24 hours. The purpose of this study was to determine the effect of adding BSF (black soldier fly) maggot flour with different levels on the performance of broiler chickens in the starter phase. The results showed that there was no significant effect (P<0.05). The provision of BSF maggot flour with levels of 0%, 5%, 10%, and 15% in the ration did not significantly affect the parameters of ration consumption, body weight gain, mortality and water consumption. However, the greater the level of BSF maggot usage, all parameters numerically increased starting from 0%, 5%, 10%, and 15% except for FCR which decreased in line with the addition of given maggot flour.